First: factor the expression - find the least common factor which is, "3" > multiply 3 by the missing terms to get "3x^2 - 12"...
3(x^2 - 4) = 0
Sec: continue to factor the expression in parenthesis = the difference of squares...
3(x + 2)(x - 2) = 0
Third: solve the two x-variables - set both parenthesis to "0"...
a. x + 2 = 0
*Isolate "x" on one side - subtract "2" from both sides (when you move a variable to the opposite side, always use the opposite sign)...
x + 2 - 2 = 0 - 2
x = - 2
b. x - 2 = 0
*Add "2" to both sides...
x - 2 + 2 = 0 + 2
x = 2
Solution: 2 and -2
2007-01-30 03:51:07
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
x = 2
2007-01-30 09:59:54
·
answer #2
·
answered by poolshark21209 2
·
0⤊
2⤋
3x^2 - 12 = 0 (Add 12 to both sides)
3x^2 = 12 (Divide both sides by 3)
x^2 = 4 (Take square root from both sides)
x = +2 or -2
QED
2007-01-30 11:27:19
·
answer #3
·
answered by CSUFGrad2006 5
·
1⤊
0⤋
3x^2-12 = 0 (Add 12 on bothsides of the equation)
+12 = +12
_____________
3x^2 = 12 (Now divide by 3 on bothsides)
3x^2 /3 = 12/3 ( now you will get :)
x^2 = 4 (Now find the squre root of both sides)
x = -2 or +2 ( This is your answer)
2007-01-30 11:00:25
·
answer #4
·
answered by Swarn 1
·
0⤊
1⤋
3x^2-12 = 0
3x^2= 12
x^2 = 12/3 = 4
x = 2 or -2
2007-01-30 10:01:05
·
answer #5
·
answered by robcraine 4
·
2⤊
0⤋
Alright..this question is fairly simple =).
First, transfer -12 to the other side. Thus, 3x^2 = 12
Then divide both sides by 3.
x^2 = 4
Square both sides.
x = + or - 2
DONE!
2007-01-30 10:06:01
·
answer #6
·
answered by Jerome Tan (Junior) 1
·
2⤊
0⤋
divide by 3
x^2-4=0
(x-2)(x+2)=o
x=2 x=-2
2007-01-30 11:40:30
·
answer #7
·
answered by nano_1992_fun 2
·
1⤊
0⤋
3x² - 12 = 0
3x² - 12 + 12 = 0 + 12
3x² = 12
3x² / 3 = 12/ 3
x² = 4
âx² = â4
x = 2
The answer is x = 2
- - - - - - - - - -s-
2007-01-30 10:42:46
·
answer #8
·
answered by SAMUEL D 7
·
0⤊
1⤋
3x^2 = 12
x^2 = 4
x = 2
2007-01-30 10:01:33
·
answer #9
·
answered by Elizabeth Howard 6
·
0⤊
2⤋